2001
DOI: 10.1034/j.1600-0765.2001.360604.x
|View full text |Cite
|
Sign up to set email alerts
|

Enamel matrix derivative (EMDOGAIN®) rapidly stimulates phosphorylation of the MAP kinase family and nuclear accumulation of smad2 in both oral epithelial and fibroblastic human cells

Abstract: In our previous study, we demonstrated that porcine enamel matrix derivative (EMD) induces p21WAF1/cip1 within 8 hours and subsequently arrests the cell cycle of human oral epithelial cells in G1 phase. In contrast, EMD markedly stimulates the proliferation of gingival fibroblasts without inducing p21WAF1/cip1. To investigate the mechanism of how EMD produces these differential effects, we have focused on the initial response of these two cell types to EMD. In epithelial cell cultures, EMD stimulated cytoskele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
137
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(158 citation statements)
references
References 23 publications
18
137
1
2
Order By: Relevance
“…However, one study found that EMD inhibited the adhesion of breast cancer (MCF-7) cells to bone matrix (79). The effects of EMD on intracellular cAMP levels differ in epithelial HeLa and SCC-25 cells (56,66). In HeLa cells, the production of PDGF-AB was enhanced by EMD, whereas no significant effect on TGF-β1 was observed (56).…”
Section: Emdogain and Malignant Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, one study found that EMD inhibited the adhesion of breast cancer (MCF-7) cells to bone matrix (79). The effects of EMD on intracellular cAMP levels differ in epithelial HeLa and SCC-25 cells (56,66). In HeLa cells, the production of PDGF-AB was enhanced by EMD, whereas no significant effect on TGF-β1 was observed (56).…”
Section: Emdogain and Malignant Cellsmentioning
confidence: 99%
“…In contrast, TGF-β1 levels in culture medium of MG-63 osteosarcoma cells were increased by EMD (39,82). In addition, EMD stimulates phosphorylation of MAP family kinases in SCC-25 cells, as does also TGF-β1 (66,83). Regarding the other cytokines, EMD enhances IL-6 production, but has no effect on the production of BMP-2 or IGF-I by MG-63 cells or HeLa cells (56,82).…”
Section: Emdogain and Malignant Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous report found that EMD prepared from developing porcine teeth possesses BMP-like and TGF-β-like activities [3,4], though the molecular mechanism is uncertain. To obtain detailed findings regarding the molecules contained in EMD, we performed 2-D PAGE analysis of EMD protein using a Zoom IPG Runner System (see materials and methods section).…”
Section: Emd Contains Amelogenin and Bmp2/4 But Not Tgf-βmentioning
confidence: 99%
“…A recent clinical review reported that EMD promotes both cementogenesis [1] and osteogenesis [2], while it has also been shown that EMD has bone morphogenetic protein (BMP) and transforming growth factor-β (TGF-β) activities [3,4], while in vitro experiments demonstrated that it stimulates osteoblast proliferation and differentiation [5,6]. EMD consists of amelogenin at nearly 90%, along with other enamel matrix proteins, such as enamelin, tuftelin, amelin, and ameloblastin [7,8].…”
Section: Introductionmentioning
confidence: 99%